Panel Discussion - Malaspina, Ermanno; Balbo, Andrea; Marciniak, Katarzyna; Axer, Jerzy; Janka, Marcus; Movrin, David (Ciceroniana On Line, 2020)
The panel discussion was moderated by Prof. Jan Miernowski (Faculty of “Artes Liberales”, University of Warsaw/Department of French & Italian, University of Wisconsin-Madison).